Inovasi Mitigasi Kebencanaan pada Desa Wisata Rindu Hati dalam Pembangunan Berkelanjutan - Novliza Eka Patrisia; Sri Indarti; Titi Darmi; Rifa i (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2026)
Rindu Hati Village as a leading tourist village in Central Bengkulu faces a paradox between tourism potential and vulnerability to annual flood disasters that threaten the sustainability of its development. This community service developed an integrated disaster mitigation innovation model that combines digital technology approaches, local wisdom, and sustainable development principles. Through a 6-month participatory action research (PAR) method, involving 40 participants (village officials, community leaders, MSMEs, and academics), the following were carried out: (1) Community-based risk mapping involving 30 MSMEs and tourism awareness groups; (2) Trial of a simple IoT-based early warning system; (3) Development of a